Impaired insulin secretion and glucose tolerance in β cell-selective Ca(V)1.2 Ca(2+) channel null mice - Schulla, Verena (Oxford University Press, 2003)
Insulin is secreted from pancreatic β cells in response to an elevation of cytoplasmic Ca(2+) resulting from enhanced Ca(2+) influx through voltage-gated Ca(2+) channels. Mouse β cells express several types of Ca(2+) channel (L-, R- and possibly P/Q-type). β cell-selective ablation of the gene encoding the L-type Ca(2+) channel subtype Ca(v)1.2 (βCa(v)1.2(–/–) mouse) decreased the whole-cell Ca(2+) current by only ∼45%, but almost abolished first-phase insulin secretion and resulted in systemic glucose intolerance. These effects did not correlate with any major effects on intracellular Ca(2+) handling and glucose-induced electrical activity. However, high-resolution capacitance measurements of exocytosis in single β cells revealed that the loss of first-phase insulin secretion in the βCa(v)1.2(–/–) mouse was associated with the disappearance of a rapid component of exocytosis reflecting fusion of secretory granules physically attached to the Ca(v)1.2 channel. Thus, the conduit of Ca(2+) entry determines the ability of the cation to elicit secretion.